TREE-RING ANALYSIS OF TEAK (TECTONA GRANDIS L. F.) FROM WESTERN GHATS OF INDIA AS A TOOL TO DETERMINE DROUGHT YEARS - Deepak, M. S.; Sinha, Satish Kumar; Rao, R. Vijendra (Emirates Journal of Food and Agriculture, 2017)
Tree-ring analysis of teak (Tectona grandis L.f.) carried out from two different sites in Western Ghats of India is reported in this paper. Teak has distinct, datable and climatic sensitive growth rings which are formed annually. Growth rings are not only cross-matching even within the radius of a tree but also between trees growing at both the sites. The tree-ring chronology of teak and climatic data revealed that there are several alternating periods of low and high to very high rainfall years. The common low rainfall years at two sites matched with the most of drought years of India. It has been found to have good potential to know rainfall pattern, mostly the drought years.